New Effective Approach to Treatment of Mandibular Angular Fracture on Background of Osteoporosis. - Likhitskyi, Oleksii (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 284